Office 365 user guide : a comprehensive guide to increase collaboration and productivity with Microsoft Office 365 - Carter, Nikkia (Packt, 2019)
Office 365 is one of the most secure and easy-to-use apps for email exchange. To help you understand the details about office365, this book will explain you different settings of Office 365, along with its extensions such as SFB, OneDrive, Sharepoint and Team.